Thyroid hormone activates Xenopus MBD3 gene via an intronic TRE in vivo - Liezhen Fu; Christin Li; Wonho Na; Yun-Bo Shi (Frontiers in Bioscience-Landmark, 2020)
Thyroid hormone (T3) is important for adult organ function and vertebrate development. Amphibian metamorphosis is totally dependent on T3 and can be easily manipulated, thus offering a unique opportunity for studying how T3 controls vertebrate development. T3 controls frog metamorphosis through T3 receptor (TR)-mediated regulation of T3 response genes. To identify direct T3 response genes, we previously carried out a ChIP (chromatin immunoprecipitation)-on-chip analysis with a polyclonal anti-TR antibody on the tadpole intestine and identified many putative TR target genes. Among them is the methyl-CpG binding domain protein 3 (MBD3) gene, which has been implicated to play a role in epigenetic regulation of cellular processes as a subunit of the Mi-2/NuRD (Nucleosome Remodeling Deacetylase) complex. We show here that MBD3 is upregulated in the intestine and tail by T3 and its expression peaks at stage 62, the climax of metamorphosis. We further show that a putative TRE within the first intron of the MBD3 gene binds to TR/RXR in vitro and in vivo, and mediates T3 regulation of the MBD3 promoter in vivo.